Hairy Root Induction on Justicia gendarussa by Various Density of Agrobacterium rhizogenes strain LB 510 - Dwi Kusuma Wahyuni; Siti Nur Hafida; Tri Muji Ermayanti; Bambang Prajoga Eko Wardoyo; Hery Purnobasuki; Edy Setiti Wida Utami (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Gandarusa (Justicia gendarussa Burm.f.) is an Indonesian medicinal plant that has many benefits as drug and male contracetive. For industrial needs, Gandarusa must be available in large quantity. Hairy root culture is one of methode to produce phytochemistry compound. The objective of the study was to examine the effect of various density of Agrobacterium rhizogenes strain LB510 on hairy roots induction of gandarusa (Justicia gendarussa Burm.f.) leaf plant. Leaf explants were inoculated in MS liquid medium with various density of OD600 = 0.1; 0.2; 0.3; 0.4; and 0.5. Explants were co-cultivated for 2 days on MS solid medium without any hormone then sub-cultured on MS solid medium containing antibiotic cefotaxim 300 ppm, in dark condition. The data were analyzed descriptively and statistically. The results showed that various density of Agrobacterium rhizogenes strain LB510 was affected the lenght of hairy roots induction of J. gendarussa Burm.f., but these was not effected toward lenght formation time and number of hairy root. The treatment of OD600 0.2 was the best treatment for hairy root induction on Justicia gendarussa Burm. f. This data could be used for optimized the quality of methode of hairy root induction.